Putu Made Restaurant Micro-Influencers Strategy - Ananda Fitria (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Today, audiences are more selective in consuming messages on social media. When influencers with millions of followers look too regulated, micro-influencers with fewer followers are judged more authentic because of the relevance of content and context. This study aims to determine the micro-influencers strategy used by Putu Made Restaurant via Instagram. The method of this research is qualitative approach with study case as the type of research. Data collection techniques are done by interview and documentation study. The result shows that the use of micro-influencers can increase engagement of Restaurant consumers on Instagram. Furthermore, this research is expected to provide a clear picture of the use of micro-influencers as the marketing communication strategies.